2022
DOI: 10.12775/jehs.2022.12.03.001
|View full text |Cite
|
Sign up to set email alerts
|

“Myroslava” and “Khrystyna” drinking mineral waters modulate the state of neuroendocrine-immune complex and metabolism in patients of Truskavets’ spa

Abstract: Background. Earlier in an experiment on rats we showed that newly created sulfate-chloride sodium-magnesium drinking mineral waters "Myroslava" and "Khrystyna" of Truskavets’ spa has a significant modulating effects on the parameters of metabolism and the autonomic nervous, endocrine and immune systems. Adhering to the principle "Ex experimento ad clinic", we continued research in this direction with the participation of patients of the resort. We showed that these mineral waters have favorable effects on meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Earlier we found effects on the neuroendocrine-immune complex and metabolism, which are common to the mineral waters "Myroslava" and "Khrystyna", instead different from the effects of Naftussya water [6,12,13]. The purpose of this article is to find the specific effects of these waters.…”
Section: Introductionmentioning
confidence: 89%
“…Earlier we found effects on the neuroendocrine-immune complex and metabolism, which are common to the mineral waters "Myroslava" and "Khrystyna", instead different from the effects of Naftussya water [6,12,13]. The purpose of this article is to find the specific effects of these waters.…”
Section: Introductionmentioning
confidence: 89%
“…Earlier we showed that the newly created sulfate-chloride sodium-magnesium drinking mineral waters "Myroslava" (5 g/L) and "Khrystyna" (10 g/L) have favorable effects on neuroendocrine-immune complex and metabolism of patients with their violations. At the same time, the influence of both waters on one constellation of parameters is similar [8,13,14], despite the twofold difference in mineralization, while on the other constellation it is different. Screening revealed specific changes in 37 parameters grouped into 5 patterns.…”
Section: Inroductionmentioning
confidence: 82%
“…"Myroslava" and "Khrystyna" mineral waters have both similar and different effects on the body of rats [1,11,12,24] and humans [8,13,14,25]. It is important that the differences are manifested not only in the severity of changes in the registered parameters, but also in their direction.…”
Section: Discussionmentioning
confidence: 99%